Предмет: Математика,
автор: Stacy1722
C3 (1е)
x^2 > log3(6)
x^2 > log3(2)+1
...
Приложения:
Ответы
Автор ответа:
0
1) x^2 > log3(6)
Выражение log3(6) равносильно 3^(y) = 6, а х² > y.
Применяя десятичные логарифмы, получаем:
10^(y*0,47712) = 10^(0,77815).
Отсюда y*0,47712 = 0,77815 или у = 0,77815 / 0,47712 = 1,63093.
Тогда х > +-√1,63093 x > +-1,27708.
2) x^2 > log3(2)+1 решается аналогично.
Выражение log3(2) + 1 равносильно 3^(y) = 2, а х² > y + 1.
Применяя десятичные логарифмы, получаем:
10^(y*0,47712) = 10^( 0,30103).
Отсюда y*0,47712 = 0,30103 или у = 0,30103 / 0,47712 = 0,63093.
Тогда х > +-√(0,63093 + 1) = +-√1,63093 x > +-1,27708.
Это вытекает из свойства логарифмов:
Выражение log3(6) равносильно 3^(y) = 3*2 = 3¹*3^(log3(2)), тогда log3(6) = 1 + log3(2)
Выражение log3(6) равносильно 3^(y) = 6, а х² > y.
Применяя десятичные логарифмы, получаем:
10^(y*0,47712) = 10^(0,77815).
Отсюда y*0,47712 = 0,77815 или у = 0,77815 / 0,47712 = 1,63093.
Тогда х > +-√1,63093 x > +-1,27708.
2) x^2 > log3(2)+1 решается аналогично.
Выражение log3(2) + 1 равносильно 3^(y) = 2, а х² > y + 1.
Применяя десятичные логарифмы, получаем:
10^(y*0,47712) = 10^( 0,30103).
Отсюда y*0,47712 = 0,30103 или у = 0,30103 / 0,47712 = 0,63093.
Тогда х > +-√(0,63093 + 1) = +-√1,63093 x > +-1,27708.
Это вытекает из свойства логарифмов:
Выражение log3(6) равносильно 3^(y) = 3*2 = 3¹*3^(log3(2)), тогда log3(6) = 1 + log3(2)
Похожие вопросы
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: халявчик